SPHERE OF DISTRIBUTION OF THE YUZ (JUZ) CLAN IN THE LAND OF SURKHAN - Mirzayeva, Mokhichexra (SCIENCE and SOCIETY, 2026)
In the article Surkhan oasis to oneself typical ethnic and social status illuminated many monographs, articles created scientist B.X.Karmysheva important information brought For example, mangit, yuz, kungirat, lakai, kipchak, ming such as Uzbek seeds and their spread about important information statement Made .
Keywords: Hisar faces; Oratepa faces; brand; ktay face; blacksmith; chagatai; resistance; time; jilantamgali; marqa child; qorapchi child; rajab child